Compact magnetohydrodynamic-enhanced cooling for dual photovoltaic-thermoelectric units: A finite element-proper orthogonal decomposition based modeling approach - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2026)
Efficient thermal management of PV-TEG (photovoltaic-thermo electric generator) units is essential for improving their conversion efficiency and operational stability. In this study, a single inclined L-shaped corrugated cooling channel is proposed for the simultaneous cooling of dual PV-TEG units under the influence of externally applied magnetic field. Finite element method (FEM) based solver is utilized to analyze the coupled influences of corrugation geometry, magnetic field strength and inlet flow rate on heat transfer performance, and PV-TEG unit performance. When comparing the lowest and maximum Reynolds number (Re), the temperature drop of PV cells for flat and wavy configurations is 5 oC for unit A (horizontal) and 9.5 oC for unit B (inclined). At the highest magnetic field strength, PV-cell temperature decreases of 3 oC, 1.2 oC, and 0.5 oC are achieved with flat A, wavy A, and flat B cooling channel layouts, whereas a temperature increase of approximately 2.5 oC is achieved with the wavy B channel scenario. For units A and B at the maximum corrugation amplitude, PV-cell temperatures drop by 2.3 oC and 4.5 oC when magnetic field effects are not present, but they drop by 0.5 oC and 2 oC when a magnetic field is applied at Ha = 60. Between the best and worst case conditions, the temperature drops for PV cells in units A and B are 10.9 oC and 17.6 oC, respectively. Using nano-enriched MGF with bottom wall corrugation can significantly reduce the temperature of the PV cell in Unit A. However, it has been shown that while the combined use of NF and corrugation enhances unit B's cooling performance, MGF reduces the system effectiveness of unit B. An effective computational procedure that provides local convective heat transfer values for both horizontal and inclined cooling channels is generated using a POD-based approach. These results are then used to determine each unit's PV-cell temperature when paired with a dual PV-TEG unit. The outcomes highlight the potential of effective cooling configurations and computational strategies for compact and high performance solar energy
Keywords: Corrugated channel; Magnetic field; Dual PV-TEG; FEM; POD